Advances of nanotechnology in osteochondral regeneration. (22nd July 2019) - Deng, Cuijun; Xu, Chang; Zhou, Quan; Cheng, Yu
Abstract: In the past few decades, nanotechnology has proven to be one of the most powerful engineering strategies. The nanotechnologies for osteochondral tissue engineering aim to restore the anatomical structures and physiological functions of cartilage, subchondral bone, and osteochondral interface. As subchondral bone and articular cartilage have different anatomical structures and the physiological functions, complete healing of osteochondral defects remains a great challenge. Considering the limitation of articular cartilage to self‐healing and the complexity of osteochondral tissue, osteochondral defects are in urgently need for new therapeutic strategies. This review article will concentrate on the most recent advancements of nanotechnologies, which facilitates chondrogenic and osteogenic differentiation for osteochondral regeneration. Moreover, this review will also discuss the current strategies and physiological challenges for the regeneration of osteochondral tissue. Specifically, we will summarize the latest developments of nanobased scaffolds for simultaneously regenerating subchondral bone and articular cartilage tissues. Additionally, perspectives of nanotechnology in osteochondral tissue engineering will be highlighted. This review article provides a comprehensive summary of the latest trends in cartilage and subchondral bone regeneration, paving the way for nanotechnologies in osteochondral tissue engineering. This article is categorized under: Implantable Materials and Surgical Technologies > Nanomaterials and Implants Nanotechnology Approaches to Biology > Nanoscale Systems in Biology Implantable Materials and Surgical Technologies > Nanotechnology in Tissue Repair and Replacement Abstract : Nanoparticle‐based strategies enhance therapeutic outcome. Nanoparticles can be divided into degradable and nondegradable nanoparticles. The degradable nanoparticles include chondroitin sulfate, collagen, PLGA, PLA, polycaprolactone, and HA, while the nondegradable nanoparticles consist of mesoporous silicon dioxide, gold nanoparticles, quantum dots, SPIOs, and lipids. Drugs, growth factors, and genetic material‐loaded nanoparticles can promote the regeneration of osteochondral tissue at sites of pathology and fracture.